Teaching the history of collective traumas and socially acute questions: trajectories of a disciplinary camp (Tempo e Argumento, 2022)
Teaching the history of collective traumas and socially acute questions was spread in historiography from the 1960s on. This contributed to dissemination of research conducted in Germany and France on the national socialist experience and the historicization of the Holocaust, whose event was framed within the field of genocide studies. In France and Brazil, reflections on this theme aimed the necessary understanding of collective traumas and their social impacts.  In our analysis, reflections on these concepts are necessary due to the trivialization of the debate about historical fascisms and other collective traumas in our present time. The concerns arising from this scenario, challenging to historians and the teaching-learning process in the classroom, motivated us to present the reflections made in this article, which presented some perspectives on teaching collective social traumas and socially acute questions.
Keywords: history teaching; collective traumas; socially acute questions